DETERMINANTS OF SELF-EFFICACY AND ITS IMPLICATIONS FOR JOB SATISFACTION OF GENERATION Z (STUDY ON GENERATION Z IN THE SOUTH TANGERANG REGION): DETERMINANTS OF SELF-EFFICACY AND ITS IMPLICATIONS FOR JOB SATISFACTION OF GENERATION Z (STUDY ON GENERATION Z IN THE SOUTH TANGERANG REGION) - Kusumawati, Yasmin; Husainah, Nazifah (PENANOMICS: International Journal of Economics, 2024)
This study was conducted with the aim of finding out and analyzing the influence of "Determinants of Self-Efficacy and Its Implications on Job Satisfaction of Generation Z (Study on Generation Z in the South Tangerang Region)". The method used is an associative method with a quantitative approach, the data analysis used is SEM-PLS with a sample of 175 generation Z respondents in the South Tangerang area. The results of the study showed that (1) that compensation for self-efficacy had a significant effect on t-statistical values (3.208) > t-table (1.96) and P values (0.001) < α (0.05) on job satisfaction. (2) that reward for self-efficacy had a significant effect on t-statistical values (5.586) > t-table (1.96) and P values (0.000) < α (0.05) on job satisfaction. (3) that the work environment on self-efficacy had a significant effect on t-statistic (3.364) > t-table (1.96) and P values (0.001) < α (0.05) on job satisfaction.(4) that compensation for job satisfaction had a significant effect on t-statistic (3.961) > t-table (1.96) and P values (0.000) > α (0.05) on job satisfaction. (5) that reward on job satisfaction had no significant effect on t-statistic (1.589) < t-table (1.96) and P values (0.112) > α (0.05) on job satisfaction. (6) that the work environment had a significant effect on job satisfaction with t-statistical values (5.348) > t-table (1.96) and P values (0.000) < α (0.05) on job satisfaction. (7) that self-efficacy on job satisfaction had no significant effect on t-statistic (0.058) < t-table (1.96) and P values (0.954) > α (0.05) on job satisfaction. (8) that compensation for job satisfaction through self-efficacy has no significant effect on t-statistic (0.055) < t-table (1.96) and P values (0.956) > α (0.05) on job satisfaction. 9) that reward for job satisfaction through self-efficacy has no significant effect as seen from t-statistical values (0.056) < t-table (1.96) and P values (0.955) > α (0.05). (10) that the work environment has no significant effect on job satisfaction through self-efficacy, as seen from the t-statistical values (0.056), t-table < (1.96), and P values (0.955) > α (0.05).